Comparison of sagittal and vertical dental changes during first phase of orthodontic treatment with MBT vs ROTH prescription - Ashok K Talapaneni; G Supraja; Mandava Prasad; Pradeep B Kommi (Wolters Kluwer Medknow Publications, 2012)
Objective: The present study was to evaluate and compare anchorage loss in sagittal, vertical dimension in incisal, molar segments and distal tipping of upper canine after first phase of orthodontic mechanotherapy utilizing MBT and ROTH philosophies. Materials and Methods: Thirty patients with class I dentoalveolar malocclusion requiring extraction of all first premolars were randomly assigned into group I and group II. Set of two lateral cephalograms (T1) and (T2) were obtained with appliance in place and after sufficient leveling and aligning respectively. Linear measurements were recorded on the tracings using Pancherz analysis. A Wilcoxon t-test was use to assess the linear changes. Results: In group I sample, upper and lower incisors retroclined during T1 - T2; by mean (SD) value of 2.267 (1.0032) mm, 2.4 (0.98) mm, respectively. Group II sample showed upper incisor proclination by -0.4 (1.404) and lower incisal retroclination by 0.06 (1.48). Upper and lower molars in group I remained stationary and group II upper and lower molars moved mesially by -1.133 (0.351) and -0.002 (0.005). In group I, upper and lower incisors extruded by -0.867 (0.611) and -0.67 (0.703), respectively, and group II the upper and lower incisors extruded by -0.9 (0.507) and -0.133 (0.639). Upper canine tipped distally during T1 - T2 in group I by -0.33° (2.609) and group II there was a change in distal tip of upper canine by -3° (3.184). Conclusion: Results from this random clinical trial showed that MBT technique effectively addressed perceived inadequacies of ROTH philosophy.